Pengetahuan Dan Sikap Perawat Terhadap Prosedur Menyuntik Yang Aman Pada Tehnik Injeksi Intravena - Supargianto, Matius Benu; Rahayu, Margareta Hesti; Hastuti, Ag Sri Oktri (STIKES Wira Husada Yogyakarta, 2023)
Abstract About 3 million of the 35 million health workers are exposed to pathogens through used needles each year. Incidents at a private hospital in Yogyakarta from 2016 to August 2021 were 5 or (27%) of all cases of used needle pricks. The aim of this research is to determine the relationship between the level of knowledge and attitudes of nurses with the implementation of compliance with safe injection procedures when administering intravenous injections. Correlation research design, using quantitative data with a cross-sectional descriptive approach, from measuring knowledge, attitudes and observations of intravenous injection procedures. The research population was all nurses in the Emergency and Outpatient Unit of Type D Hospital under the management of one of the foundations in Yogyakarta, totaling 38 people. The sampling technique is non-probability sampling, namely saturated sampling, where all members of the population are sampled. Data collection methods used are questionnaires and observation. Most of the nurses 55.3% had fairly good knowledge, almost half had good knowledge and 2.6% had poor knowledge. Most of 65.8% behaved well, almost half 31.6% behaved quite well and a small portion of 2.6% behaved not well. Most of the 63.2% are of good practice, almost half of 36.8% are of moderately good practice and none of them are of poor value. Spearman test results, there is a significant, positive and sufficient relationship between the level of nurse knowledge and compliance with safe injection procedures when administering intravenous injections, with a p value of 0.004 (< 0.05). There is a significant, positive and sufficient relationship between nurses' attitudes and compliance with safe injection procedures when administering intravenous injections, with a p value of 0.018 (< 0.05). Conclusion: the level of knowledge, and attitudes influence the implementation of safe injection procedures in intravenous injection. Suggestion: Hospitals provide opportunities for further study, training, monitoring and evaluation, providing facilities, increasing interest in learning, and awareness of nurses to comply with regulations. Keywords: knowledge, attitude, adherence to injection procedures